Cost-effectiveness of metformin in the prevention of Type 2 diabetes mellitus: A systematic review - Thuy, Nguyen Thi Thu; Nghi, To Hue; Thanh, Tran Ngoc Thien; Duong, Huynh Hai; Huy, Nguyen Cao Duc (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2024)
Background and aims: Type 2 diabetes mellitus (T2DM) is a common metabolic disorder with serious complications. Prediabetes treatment with metformin or lifestyle changes has been shown to delay the progression of prediabetes to T2DM, thus alleviating the overall economic burden associated with T2DM. This systematic review was conducted to evaluate the cost-effectiveness of metformin in the treatment of prediabetes. Methods and results: A PRISMA-guided systematic review was performed on databases: Pubmed, Cochrane, and Embase with appropriate keywords and phrases. CHEERS checklist was used to evaluate the studies’ quality. Research characteristics and outcomes were examined, and Incremental cost-effective ratio (ICER) was converted to the USD 2020. With 402 articles identified through the search strategies, 16 articles that met the selection criteria were included for analysis in this review. All articles were deemed to be of relatively good quality according to CHEERS checklist. These analyses were conducted in developed countries from different perspectives and time frames. One of 16 studies revealed metformin as cost-saving compared to placebo, while the remaining studies reported metformin to be cost-effective compared to placebo, no intervention, or standard care, with ICERs below the willingness-to-pay threshold (ranging from 457/QALY to 164,621/QALY). However, conclusions regarding the cost-effectiveness of metformin versus lifestyle changes varied depending on different perspectives and program intensity. Conclusion: Metformin was dominant or cost-effective compared to placebo and no interventions in the treatment of prediabetes. However, the question about cost-effectiveness of metformin versus lifestyle change remained a subject of controversy among the studies. Further investigation into the cost-effectiveness of metformin compared to lifestyle change was recommended, particularly in developing countries where there is a high prevalence rate and limited healthcare resources.